Exploring the Pharmacokinetics and Gut Microbiota Modulation of Hesperidin and Nobiletin from Mandarin Orange Peel in Experimental Dogs: A Pilot Study - Jun Nakahigashi; Makoto Kurikami; Satomi Iwai; Sadahiko Iwamoto; Shou Kobayashi; Eiji Kobayashi (Metabolites)
Background/Objectives: Mandarin orange peel (MOP) is recognized for its traditional medicinal properties due to its high flavonoid content. This study aimed to analyze MOP harvested in Japan for specific bioactive compounds and to explore its health applications in dogs, including effects on gut microbiota and cognitive symptoms. Methods: Flavonoid content (particularly hesperidin and nobiletin) of MOP was measured. High-flavonoid MOP was then incorporated into gelatin cubes. In the time–course blood concentration study, experimental beagle dogs received a single oral dose (4 g). For intestinal microbiota analysis and blood biochemical tests, beagle dogs were administered 1 g twice daily. For the Demonstration Test, older dogs (a 14-year-old female Shiba Inu, a 14-year-old female Miniature Dachshund, and a 19-year-old male Miniature Dachshund) were administered 1 g twice daily. Analysis included microbiota profiling via 16S rDNA sequencing and observational assessment of cognitive indicators in a pilot study involving senior dogs with Alzheimer’s disease. Results: The MOP powder contained 9.3% hesperidin in early-ripening varieties (October harvest) and 6.9% in ripe varieties (December harvest). Nobiletin content was 41 mg/100 g (0.041%) and 35 mg/100 g (0.035%) for the early and late harvests, respectively. Administration of MOP-enriched gelatin cubes reduced Fusobacteriaceae and increased Eggerthellaceae. Cognitive symptoms like howling and counterclockwise turning showed improvement in senior dogs (n = 3). Conclusions: This study provides preliminary support for the potential health benefits of MOP in canine dietary applications, particularly for gut health and cognitive function. Improvement in cognitive symptoms may be due to the anxiolytic effects of mandarin peel.